Exploring the educative role of judges' sentencing remarks: an analysis of remarks on child exploitation material. Issue 6 (2nd November 2018) - Hunn, Charlotte M.; Cockburn, Helen; Spiranovic, Caroline; Prichard, Jeremy
Abstract : The online viewing of child exploitation material (CEM) is a seemingly intractable problem. Evidence suggests that CEM is viewed not only by the paedophilic 'other',  but by people without prior offending histories or pre-existing sexual interests in children. Studies emphasise the role of offence-supportive attitudes in enabling first-time offending. Relatedly, nascent research indicates that some sections of the Australian community express ambivalence about the harms involved in viewing such material. Taking a crime prevention perspective, this article considers the need and value of tackling such attitudes and the educative role that judges' sentencing comments may play. In doing so, this article presents a content analysis of judicial comments from Victoria and Tasmania. Encouragingly, results show that judges provide some explanation of the harms involved in most instances. Yet,  some of the explanations that judges give may be perpetuating, rather than reducing, ambiguity about the wrongfulness of 'just' viewing CEM online.